Compact Dual-Wideband Bandpass Filter Using a Novel Multiple-Mode Resonator - Xu, Jin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents a novel dualwideband bandpass filter (BPF) structure, which consists of a two-end shorted stepped-impedance resonator with two pairs of non-identical steppedimpedance open stubs (SIOSs) and a uniformimpedance open stub (UIOS) symmetrically loaded on its high impedance section. The designed BPF has a directly coupled configuration, which can also introduce transmission zero (TZ) for filter design. The loaded SIOSs and UIOS not only excite multiple resonant modes but also introduce multiple TZs. After carefully arranging these resonant modes and TZs, the TZs can divide multiple resonant modes into multiple useful groups, which can be utilized to exploit two wideband passbands. The TZs between two passbands can improve passband selectivity and the band-toband isolation. As an example, a dual-wideband BPF centered at 1.57 / 5.59 GHz with -3 dB fractional bandwidth of 53% by 16% is designed and fabricated. The fabricated filter has a compact size of 0.16?g × 0.106?g. The measured results also exhibit a low insertion loss, good return loss and wide stopband.